2019
DOI: 10.1002/1438-390x.1023
|View full text |Cite
|
Sign up to set email alerts
|

Big cats at large: Density, structure, and spatio‐temporal patterns of a leopard population free of anthropogenic mortality

Abstract: Human impact is near pervasive across the planet and studies of wildlife populations free of anthropogenic mortality are increasingly scarce. This is particularly true for large carnivores that often compete with and, in turn, are killed by humans. Accordingly, the densities at which carnivore populations occur naturally, and their role in shaping and/or being shaped by natural processes, are frequently unknown. We undertook a camera-trap survey in the Sabi Sand Game Reserve (SSGR), South Africa, to examine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
74
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(83 citation statements)
references
References 71 publications
(126 reference statements)
8
74
1
Order By: Relevance
“…Although our results suggested that prey density and vulnerability at the home range scale (i.e. per capita resource availability) did not affect the magnitude of dietary specialization exhibited by individuals, intraspecific competition, possibly for space and mates more than food (Balme, Rogan, et al, ), still likely contributed to some individuals specializing. The high density of leopards in the SSGR is unusual; most leopard populations, even those in comparable savanna habitats, are depressed by anthropogenic perturbation (Balme, Rogan, et al, ).…”
Section: Discussioncontrasting
confidence: 55%
See 4 more Smart Citations
“…Although our results suggested that prey density and vulnerability at the home range scale (i.e. per capita resource availability) did not affect the magnitude of dietary specialization exhibited by individuals, intraspecific competition, possibly for space and mates more than food (Balme, Rogan, et al, ), still likely contributed to some individuals specializing. The high density of leopards in the SSGR is unusual; most leopard populations, even those in comparable savanna habitats, are depressed by anthropogenic perturbation (Balme, Rogan, et al, ).…”
Section: Discussioncontrasting
confidence: 55%
“…Most extant indigenous mammal species are present on the reserve, including the entire large carnivore guild, as well as their primary prey base (Radloff & Du Toit, ). Estimated leopard population density, based on spatial capture–recapture modelling, is 11.8 ± 2.6 leopards/100 km 2 and close to capacity (Balme, Rogan, et al, ).…”
Section: Methodsmentioning
confidence: 87%
See 3 more Smart Citations